Technologies Used in the Study of Advanced Mathematics by Students who Are Visually Impaired in Classrooms: Teachers' Perspectives. (July 2015) - DePountis, Vicki M.; Pogrund, Rona L.; Griffin-Shirley, Nora; Lan, William Y.
Introduction: This research examined the perspectives of teachers of students who are visually impaired regarding the use and effectiveness of high-tech assistive technology purported to assist visually impaired students in advanced mathematics. Methods: The data for this study were collected via a mixed-methods online survey distributed through professional networks to reach teachers with experience supporting students who are braille readers in advanced mathematics. A device matrix was used to ask participants about three interrelated issues. First, which of the 35 assistive technologies presented did they use to aid students? Second, how was the technology implemented? And third, how did they rate the effectiveness of each device used? Open-response items provided space for additional tools and other feedback. Results: A total of 82 surveys were completed through the device matrix question. Results conclusively indicated that 20 of the 35 technologies were used; of these, 13 were used regardless of subject. More than half of the participants indicated that the same four technologies were implemented for student information access during class, guided practice, and independent practice. Participants recommended seven technologies not included in the device matrix through the open-response questions. Discussion: This survey revealed that teachers of visually impaired students are using assistive technology for multiple functions. A core set of 13 devices emerged, as well as varying subsets for specific tasks across different subjects. Limitations of the study were the small sample size and possible survey fatigue. Implications for practitioners: By examining the uses of technology presented in this article, teachers can determine which assistive technology might be worth exploring to use for preparation of materials for students and which to teach others to use independently for reading or preparation of assignments in advanced mathematics courses.